2018
DOI: 10.3389/fimmu.2018.02759
|View full text |Cite
|
Sign up to set email alerts
|

Combination Strategies to Optimize Efficacy of Dendritic Cell-Based Immunotherapy

Abstract: Dendritic cells (DCs) are antigen-presenting cells (APCs) that are essential for the activation of immune responses. In various malignancies, these immunostimulatory properties are exploited by DC-therapy, aiming at the induction of effective anti-tumor immunity by vaccination with ex vivo antigen-loaded DCs. Depending on the type of DC-therapy used, long-term clinical efficacy upon DC-therapy remains restricted to a proportion of patients, likely due to lack of immunogenicity of tumor cells, presence of a str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(38 citation statements)
references
References 133 publications
0
37
0
Order By: Relevance
“…However, as discussed earlier several issues should be addressed before becoming mainstream in cancer therapy. Current clinical trials involving different types of tumors (as in Table 1 ) are currently exploring the significance of the DC vaccine as a monotherapy or in combination with other interventions in different types of tumors as metastatic melanoma [41] , breast cancer [42] , and prostate cancer [36] .…”
Section: Dendritic Cell-based Vaccine Therapy and Its Different Implementioning
confidence: 99%
“…However, as discussed earlier several issues should be addressed before becoming mainstream in cancer therapy. Current clinical trials involving different types of tumors (as in Table 1 ) are currently exploring the significance of the DC vaccine as a monotherapy or in combination with other interventions in different types of tumors as metastatic melanoma [41] , breast cancer [42] , and prostate cancer [36] .…”
Section: Dendritic Cell-based Vaccine Therapy and Its Different Implementioning
confidence: 99%
“…Animal experiments support the combination of the EP4 antagonist E7046 (ER0886046) with anti-CTLA4 in a mouse melanoma B16F10 model and with anti-PD-1 or anti-PD-L1 antibodies in a mouse colon cancer CT26 model. Higher antitumor efficacies were demonstrated in combination, compared with E7046 or the ICI antibody alone (44). Figure 2 illustrates the opportunity to introduce EP4 antagonist therapy with ICIs, which may cooperatively interact leading to an efficient C-IC.…”
Section: Roles Of Pge 2 and Ep4 In C-ic And Perspectives On Ep4 Antagmentioning
confidence: 99%
“…The combination of radiotherapy and/or chemotherapy with the EP4 antagonist is thought to synergistically accelerate the C-IC. Simultaneous increases in the cDC population by EP4 therapy and the production of DAMPs through therapy-producing ICD in tumors are essentially required for the effective production of tumor-specific effector CD8 + T cells (44) (Figure 2).…”
Section: Roles Of Pge 2 and Ep4 In C-ic And Perspectives On Ep4 Antagmentioning
confidence: 99%
“…Several sources of tumor antigens (mRNA, peptides, proteins or whole tumor cell lysate) can be used to load DCs (107). Because TAAs are difficult to identify in mesothelioma (thus excluding peptides as best source), and adequate tumor tissue is rarely obtained from mesothelioma patients (108,109), an allogenic tumor lysate has been developed (110). Results from a first-inhuman clinical trial involving nine MPM (non-progressive after at least 4 cycles of chemotherapy) showed that this approach is safe (no dose-limiting toxicities were established) and led to radiological responses and promising survival data, with median PFS of 8.8 months and median OS not reached (110).…”
Section: Vaccinesmentioning
confidence: 99%